Pengaruh Ukuran Perusahaan, dan Leverange Terhadap Praktik Income Smoothing pada Bank Syariah - Syawal Harianto; Haris Al Amin; Yusmika Indah (Jurnal EMT KITA, 2020)
This research is to know the effect of firm size, and financial leverage to Income Smoothing practices is Islamic Banks.Â  The data used is the secondary data with sourced from annual report data published by Islamic commercial banks and syariah business unit during 2016-2018 periods, samples research are 54 (fifty four) bank. Data analysis method using eviews with the fixed effect model. The result of the research shows that the simultan firm size and financial leverage have significant effect on Income Smoothing in Islamic banks.the partially, firm size an financial leverage has a positive and significant effect on income smoothin practices in Islamic banks City. The determination test result is 55%.